The Effect Of Non-Medicated Urea Molasses Block (UMB) And Medicated Urea Molasses Block (MUMB) On Growth, Carcass Characteristics, Blood Metabolites, And Control Of Gastro-Intestinal Nematode Infection On The Goat (Capra Sp) In Malaysia - Charkhanehsari, Hamed Kioumarsi (2011)
This research was carried out to examine the effects of introducing molasses/mineral feed blocks beside the use of medicated blocks on growth, efficiency, carcass characteristics, blood metabolites and control of gastro-intestinal nematode infection in grazing goats in Malaysia. Results shows that molasses/mineral feed blocks and medicated blocks have significant effects (p<0.05) on final weight, average daily gain, carcass length, hot carcass weight, weight of 9th, 10th and 11th rib area, backfat thickness, body wall thickness, ribeye area- REA, eye muscle width, eye muscle depth, internal organs, internal fats and all major carcass parts. At the end of the experiment, the blood was taken and analyzed to measure pathological and biochemical parameters.